(untitled) (Journal of Hama University, 2020)
The purpose of this study is to determine the impact of the banking deposits structure on the return of the loan portfolio of private commercial banks listed on the Damascus Securities Exchange, where the study included the entire research community, consisting of 11 private commercial banks during the period (2012: Q1 – 2018: Q3). To achieve the objective of the research, a mathematical model was designed which includes: the return of the loan portfolio as a dependent variable and the deposits structure (current deposits, saving deposits, timing deposits) were defined as independent variables and bank size as a controlled variable. The results of the research, based on the analysis of the cross-sectional data matrix (Panel -data) for private commercial banks using the statistical analysis program (Eviews 10), showed no significant effect of the relative weight (for current deposits, saving deposits and timing deposits), Which indicates that the banks weren’t able to invest their deposits well and lost a large part of the profits during the period of study. The study also showed a negative significant effect on the bank size on the loan portfolio return, which indicates that there is a liquidity surplus in these banks, and as a result of not employing this liquidity it had lost huge profits..